Respostas
respondido por:
6
-3x - 2y = 8 (a)
x - 5y = 3 (b)
Da equação (b)
x = 3 + 5y (c)
Substituindo em (a)
-3(3 + 5y) - 2y = 8
Resolvendo a equação:
-9 - 15y - 2y = 8
-17y = 8 + 9
-17y = 17
y = -1
Em (c)
x = 3 + 5y
x = 3 + (-5)
x = -2
x - 5y = 3 (b)
Da equação (b)
x = 3 + 5y (c)
Substituindo em (a)
-3(3 + 5y) - 2y = 8
Resolvendo a equação:
-9 - 15y - 2y = 8
-17y = 8 + 9
-17y = 17
y = -1
Em (c)
x = 3 + 5y
x = 3 + (-5)
x = -2
jujuda13:
obrigada, me ajudou muito!
respondido por:
2
-3x-2y=8
x-5y=3
--------------
x=5y+3 -3(5y+3)-2y=8
-15y -9 -2y = 8
-17y=8+9
-17y=17
-y= 17/17
-y=1 (-1)
y= -1
ai substitui
x=5y+3
x=5(-1)+3
x= -5+3
x= -2
x = -2 e y = -1
x-5y=3
--------------
x=5y+3 -3(5y+3)-2y=8
-15y -9 -2y = 8
-17y=8+9
-17y=17
-y= 17/17
-y=1 (-1)
y= -1
ai substitui
x=5y+3
x=5(-1)+3
x= -5+3
x= -2
x = -2 e y = -1
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás